Evaluation of Chitosan and Potato Starch as Stabilizers to Improve the Mechanical and Water Durability Properties of Printable Earth-Based Matrices Reinforced with Sisal Fibers - Zavaleta, D.; Ñañez, R.; Silva, G.; Kim, S.; Ruiz, G.; Pando, M.A.; Nakamatsu, J.; Aguilar, R. (Trans Tech Publications Ltd, 2023)
Due to economic, sustainable, and aesthetic benefits, academia and the construction industry are exploring the use of earth in modern construction is being widely studied. Unfortunately, earth as a construction material has low mechanical, poor water durability resistance, and the potential to swell and crack. Therefore, this paper evaluates chitosan and potato starch, natural biodegradable polymers, as stabilizers to improve mechanical strength and water durability resistance of printable earth-based matrix reinforced with sisal fibers. Although the test results indicated that the chitosan had a better performance as an earth stabilizer than potato starch, adding both stabilizers resulted in earthen composites with higher compressive strength and lower water permeability. These results demonstrate the feasibility of using natural stabilizers to improve the performance of earth-based materials for 3D printing without affecting their printability capacities.
Keywords: Durability; Materials science; SISAL; Chitosan; Composite material; Compressive strength; Water resistance; Starch; Natural fiber; Fiber; Chemical engineering; Chemistry; https://purl.org/pe-repo/ocde/ford#2.05.01